PRODUKTIVITAS DUA JENIS JANGKRIK LOKAL Gryillus testaceus Walk. DAN Gryllus mitratus Burn. (Orthoptera: Gryllidae) YANG DIBUDIDAYAKAN - P Widyaningrum; Asnath M Fuah; DTH Sihombing (Research Center for Biology-Indonesian Institute of Sciences, 2000)
Study on the productivity of two species of local crickets; Gryllus testaceus Walk and Gryllus mitratus Burn which are generally found in the local market have been conducted with the main aim at obtaining information on the capability of those species in producing eggs including the length of production cycles.Three levels of box square density (50 female/box,100 female/box and 150 female/box) and two levels of additional feed (green master and papay leaves) were used as treatments.The results showed that the number of eggs produced by G.mitratus were larger with longer production cycles compared to those of G.testaceus. Species and density has highly significant effects on egg production and feed consumption, whereas,additional feed significantly influencing egg production and feed consumption of the two species.The use of green master as additional feed resulted in a higher egg production than those given papay leaves.